The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/1415-790x201400010003eng
|View full text |Cite
|
Sign up to set email alerts
|

Heavy physical work and low back pain: the reality in urban cleaning

Abstract: Low back pain (LBP) is a major public health issue. There is lack of research on this disorder affecting urban cleaning workers. A cross-sectional study was conducted to describe the prevalence of LBP, occupational and extra-occupational characteristics, as well as associated factors in these workers. A census was performed with 624 workers in Salvador, Brazil, using a questionnaire administered by an interviewer in 2010. Cases of LBP were defined by reported symptoms of pain in the previous 12 months, lasting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
2
0
3
Order By: Relevance
“…Furthermore, Burdorf et al [26] have found that sedentary workers who have to work in non-neutral positions are more at risk of LBP. Pataro and Fernandes (2014) state that LBP was associated with longer working hours, flexion and trunk rotation. Dynamic activity such as walking or running served as a protective factor [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Burdorf et al [26] have found that sedentary workers who have to work in non-neutral positions are more at risk of LBP. Pataro and Fernandes (2014) state that LBP was associated with longer working hours, flexion and trunk rotation. Dynamic activity such as walking or running served as a protective factor [27].…”
Section: Discussionmentioning
confidence: 99%
“…Pataro and Fernandes (2014) state that LBP was associated with longer working hours, flexion and trunk rotation. Dynamic activity such as walking or running served as a protective factor [27]. Moreover, Caban et al (2014) found that the percentage of workers with ankle and knee pain was significantly higher among workers who join regular moderate and vigorous PA programs than among those who do not attend such programs [28].…”
Section: Discussionmentioning
confidence: 99%
“…Quanto a região do corpo mais acometida, a lombar foi a mais ressaltada entre o grupo pesquisado, contudo, a região do pescoço e do dorso também apresentaram destaque. Dados compatíveis foram encontrados nos estudos de Mederiros et al (2014) e Pataro;Fernandes (2014).…”
Section: Discussionunclassified
“…Estas lesões correspondem a "uma síndrome que vem provocando sequelas irreversíveis aos trabalhadores que podem implicar invalidez permanente. A dor e a fragilidade nos membros ou na coluna podem se tornar crônicas e impossibilitar até mesmo a realização das tarefas mais simples e banais do cotidiano" (MORAES;BASTOS, 2013, p. 3 (CARDOSO et al, 2014;DARTORA;SANTOS, 2014;HANSELL et al, 2014;NASCIMENTO et al, 2014;SILVA, 2015;PATARO;FERNANDES, 2014;PINHO;NEVES, 2010;PORTA et al, 2009;SOUSA, V. et al, 2015;VELLOSO;GUIMARÃES, 2013). "Cabe ressaltar que os riscos mencionados não agem sobre o trabalhador de forma isolada.…”
Section: Introductionunclassified
See 1 more Smart Citation